Into the Dynamics of a Supramolecular Polymer at Submolecular Resolution - Davide Bochicchio; Matteo Salvalaglio; Giovanni M. Pavan (Nature Communications, 2017)
Accessing the dynamics of soft self-assembled materials at high resolution is very difficult. Here the authors show atomistic and coarse-grained modelling combined with enhanced sampling to characterize the molecular mechanisms and kinetics of monomer exchange in synthetic supramolecular polymers.